„Ostra broń” – agentura celna. Tajni współpracownicy w więzieniach i aresztach śledczych w latach 1944–1956 - Wołoszyn, Jacek (Pamięć i Sprawiedliwość, 2010)
Having had Polish society under systematic observation, the security apparatus was able to carry out its basic operational activity which was maintaining control over people. Among those under surveillance, there were not only ordinary people but also those being imprisoned in detention centres/ custodies and in jails. They were deeply infiltrated by a group of informers, the so-called cell agent network (prisoners-stoolies) recruited among detainees. That special category of the TW (TW – tajny współpracownik, secret collaborator) was considered to be one ofthe most important elements of the operational activity. All pieces of information they managed to gather provided investigation functionaries with the solid base for further investigations, interrogations, arrestments, new trials and litigations. Those prison secret collaborators, operating within particular cells, were simultaneously fulfilling two categories of tasks: while they were acting like informants supplying investigation officers with information gained from observation and chats conducted with detainees, they also – by playing psychological game – incitedthem to particular behaviours. For instance, they made selected inmates accept all the accusations brought against them by imputing the acts never committed.What is more, cell agents reported to the SB not only their “friends” from jail but also the prison staff.